How bio-filaments twist membranes. Issue 26 (13th June 2016) - Fierling, Julien; Johner, Albert; Kulić, Igor M.; Mohrbach, Hervé; Müller, Martin Michael
Abstract : We study the deformations of a fluid membrane imposed by adhering stiff bio-filaments due to the torques they apply. Abstract : We study the deformations of a fluid membrane imposed by adhering stiff bio-filaments due to the torques they apply. In the limit of small deformations, we derive a general expression for the energy and the deformation field of the membrane. This expression is specialised to different important cases including closed and helical bio-filaments. In particular, we analyse interface-mediated interactions and membrane wrapping when the filaments apply a local torque distribution on a tubular membrane.